The PJBL for Arabic Speaking Skills and Student Confidence: A Quasi-Experimental Study at the University of Kiai Abdullah Faqih Gresik - Muhammad 'Ainul Haq; Friendis Syani Amrulloh; Imam Nur Aziz (Prodi Pendidikan Bahasa Arab Sekolah Tinggi Agama Islam As-Sunnah, 2025)
Mastery of Arabic speaking skills (maharah al-kalam) represents a central objective in language education. Yet, it remains particularly difficult to achieve in non-native learning contexts, where learners frequently experience low self-confidence and anxiety about making errors. Although Project-Based Learning (PjBL) has been conceptually recognized as a learner-centered approach capable of addressing both linguistic and affective challenges, empirical investigations examining its combined influence on speaking proficiency and self-confidence among female Arabic learners in Indonesia are still limited. This study examined the effectiveness of the PjBL model in improving Arabic speaking skills and self-confidence among female students enrolled in an Arabic Language Education program. A quasi-experimental method with a non-equivalent control group design was employed, involving 40 participants divided into an experimental group (n=20) and a control group (n=20) over a six-week instructional period. Data were gathered through speaking performance tests and self-confidence questionnaires administered before and after the intervention, and analyzed using t-tests and the Mann–Whitney U test. The results indicated that the experimental group achieved greater gains than the control group, with a moderate improvement in speaking skills (N-Gain = 0.53) and a large effect size (Cohen’s d = 1.45). Additionally, students’ self-confidence increased significantly from a low to a high level. These findings confirm that PjBL is an effective instructional approach for simultaneously enhancing Arabic speaking competence and learner self-confidence.